Narrative Techniques and Aims of the Discourse on Military Expeditions and Coastal Defense in Ramon Muntaner’s "Crònica" (1328) - Orazi, Veronica (Approaches to New Trends in Research on Catalan: Studies Linguistics, Literature, Education and Cultural Studies, 2021)
Ramon Muntaner was not a professional writer and composed only one work. He was rather a captain, a diplomat, a governor, a man very close to the Crown. His personal experience of war is witnessed in his Chronicle, according to two different narrative mechanisms: the technologization and the literarization of the described events. The defense during the Crusade against the Crown of Aragon (1283-1285) concretizes the author’s peculiar dichotomy technologization-literarization of history, emphasizes a perfect military strategy and the final victory; the narration of expansion through the Mediterranean is developed both in the conquest of Djerba and the Kerkennah Islands (1309-1314) and in the campaign of Sardinia and Corsica (1323-1324), but from two different points of view: the former offers an exemple of self celebration, which is possible because of its relative relevance if compared with other epochal events related in work; the latter is based on the documentation that the admiral Carrós sent to the King, as Muntaner did not participate in it. Finally, the expedition of the Catalan Company to the East (1303-1308) synthetises all these features and represents one of the highest moments of the whole Crònica.
Keywords: Invasions chrétiennes – Djerba; Muntaner; Ramón (1265-1336)

Quatre ulls i deu orelles: Ramon Muntaner, capità de Gerba = Four Eyes and ten Ears: Ramon Muntaner, Captain of Djerba - Àvila, Josep Antoni Aguilar (Revista de lenguas y literaturas catalana, gallega y vasca, 2021)
The present paper analyses chapters 248-265 of Ramon Muntaner’s Chronicle, devoted to the years 1309-1315, in which the Catalan soldier and chronicler acted as captain of Djerba on behalf of King Frederick III of Sicily. Thus, firstly, it examines the main aspects of Muntaner’s account of the events comprised between the conquest of Djerba by Admiral Roger of Lauria (1284) and the turmoils caused by a series of local revolts against Catalan-Sicilian rule (1306-1311), which he had to quell during his governorship of the island. Secondly, it considers the foremost traits Muntaner ascribes to his own character in this section of the book, paying specific attention to the literary devices he employs in order to build this literary self characterization. Thirdly and lastly, it focuses on the tactics and military dispositions adopted by Muntaner during the Djerban campaign, which are studied in the light of some significant medieval treatises on warfare. The carried out analysis highlights Muntaner’s intent to vindicate his success in Djerba as a great victory for the House of Aragon, and, therefore, to present himself as a true champion of the Catalan-Aragonese princes’ cause.
Keywords: Muntaner; Ramón (1265-1336)